Relationship Between Body Mass Index, Duration of Diabetes Mellitus, and Physical Activity Degree with The Incidence of Diabetic Retinopathy in Type 2 Diabetes Mellitus Patients at Praya Hospital - Asary, Teguh Mayadi; Effendi, Raden Gunawan; Khairunnisai T.; Adnyana, I Gede Angga (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Diabetes Mellitus is a chronic condition that leads to complications and premature death worldwide. Diabetic retinopathy is a posterior segment anomaly and one of the most prevalent microvascular problems. The purpose of this study is to examine the link between body mass index, diabetes duration, and level of physical activity with the incidence of diabetic retinopathy in Praya Regional Hospital's type 2 diabetes patients. This study employed a case control design and observational quantitative analytical research as its methodology. Purposive sampling is the method employed, and it involves questionnaire completion, interviews, and medical records. The data was analyzed using the Chi Square test, with a significance level of p < 0.05. The study comprised 54 samples in each case and control group, for a total sample size of 108. Body mass index was substantially linked with the development of diabetic retinopathy (p=0.013). Diabetic retinopathy was significantly associated with diabetes duration (p-value = 0.001). The degree of physical activity had no significant association with the development of diabetic retinopathy (p-value = 0.823). At Praya Regional General Hospital, the incidence of diabetic retinopathy in persons with type 2 diabetes mellitus is linked to body mass index and diabetes duration, but not to physical activity level.